2023
DOI: 10.1002/anie.202300387
|View full text |Cite
|
Sign up to set email alerts
|

C‐Bound or O‐Bound Surface: Which One Boosts Electrocatalytic Urea Synthesis?

Abstract: The electrocatalytic C−N coupling from carbon dioxide and nitrate under ambient conditions is kind of sustainable and promising alternative method for urea synthesis. To date, the influence of catalyst surface properties on molecular adsorption configuration and electrocatalytic urea synthesis activity is unclear. In this work, we proposed that the urea synthesis activity is closely linked with the localized surface charge on bimetallic electrocatalysts, it is found that a negatively charged surface induces C‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 52 publications
1
39
0
1
Order By: Relevance
“…The second C−N bond is constructed by coupling another * NO 2 with * CO 2 NH 2 (obtained from the hydrogenation of * CO 2 NO 2 ) to form * CO 2 NO 2 NH 2 , followed by the final production of urea after several PCET steps. More importantly, it is also found that the binding configuration of CO 2 has a great influence on urea formation [17] . For example, * COOH with C atom bound on the negatively charged surface is more beneficial for the C−N coupling and urea production than those of * OCHO with O atom bond on the positively charged surface.…”
Section: The Reaction Pathways Of Urea Formationmentioning
confidence: 96%
See 2 more Smart Citations
“…The second C−N bond is constructed by coupling another * NO 2 with * CO 2 NH 2 (obtained from the hydrogenation of * CO 2 NO 2 ) to form * CO 2 NO 2 NH 2 , followed by the final production of urea after several PCET steps. More importantly, it is also found that the binding configuration of CO 2 has a great influence on urea formation [17] . For example, * COOH with C atom bound on the negatively charged surface is more beneficial for the C−N coupling and urea production than those of * OCHO with O atom bond on the positively charged surface.…”
Section: The Reaction Pathways Of Urea Formationmentioning
confidence: 96%
“…More importantly, it is also found that the binding configuration of CO 2 has a great influence on urea formation. [17] For example, *COOH with C atom bound on the negatively charged surface is more beneficial for the CÀ N coupling and urea production than those of *OCHO with O atom bond on the positively charged surface. In addition, NO 2 À is also used as N feedstock to synthesize urea.…”
Section: Electrochemical Co-reduction Of Co 2 and Nmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be highly interesting to study the influence of a modified SEI with different conductivity on the observed non-linear kinetics in the future. SEI modification aiming for improved anode stability is increasingly being studied, [45,46] however, we are not aware of any systematic study yet. We expect that the observed non-linear behavior will strongly depend on the type of SEI.…”
Section: Wwwadvancedsciencecommentioning
confidence: 99%
“…By contrast, electrocatalytic technology to reduce N 2 and CO 2 to urea is a mild and efficient technology to turn waste into treasure. [13][14][15][16][17][18][19][20][21][22][23][24][25] Zhang and coworkers [26] prepared a heterostructures catalyst to promote the adsorption of noble gases by designing a space charge region; Li and co-workers [27] investigated the ability of 2D metal borides to electrosynthesize urea under ambient conditions and promote urea production by inhibiting the side reaction of N 2 reduction to NH 3 . Wang and co-workers [28] designed a PdCu nanoparticle grown on titanium dioxide to form C-N bond through thermodynamic spontaneous coupling between *N=N* and *CO.…”
Section: Introductionmentioning
confidence: 99%